Fermentable short chain carbohydrate (FODMAP) content of common plant‐based foods and processed foods suitable for vegetarian‐ and vegan‐based eating patterns. Issue 3 (23rd February 2018) - Tuck, C.; Ly, E.; Bogatyrev, A.; Costetsou, I.; Gibson, P.; Barrett, J.; Muir, J.
Abstract: Background: The low FODMAP (fermentable, oligo‐, di‐, mono‐saccharides and polyols) diet is an effective strategy to improve symptoms of irritable bowel syndrome. However, combining the low FODMAP diet with another dietary restriction such as vegetarianism/veganism is challenging. Greater knowledge about the FODMAP composition of plant‐based foods and food processing practices common to vegetarian/vegan eating patterns would assist in the implementation of the diet in this patient population. The present study aimed to quantify the FODMAP content of plant‐based foods common in vegetarian/vegan diets and to investigate whether food processing can impact FODMAP levels. Methods: Total FODMAP content was quantified in 35 foods, including fructose‐in‐excess‐of‐glucose, lactose, sorbitol, mannitol, galacto‐oligosaccharide and total fructan, using high‐performance‐liquid‐chromatography and enzymatic assays. The effects of cooking, sprouting, pickling, fermentation, activation and canning on FODMAP content were assessed. The Monash University criteria to classify foods as low FODMAP was used. Results: Of the 35 foods, 20 were classified as low FODMAP, including canned coconut milk (0.24 g serve –1 ), dulse (0.02 serve –1 ), nutritional yeast (0.01 serve –1 ), soy cheese (0.03 serve –1 ), tempeh (0.26 serve –1 ), wheat gluten (0.13 serve –1 ) and wheat grass (0.05 serve –1 ). No FODMAPs were detected in agar‐agar, egg replacer, vegan egg yolk, kelp noodles and spirulina. Food processing techniques that produced the greatest reduction in FODMAP content included pickling and canning. Conclusions: The present study provides a greater FODMAP composition knowledge of plant‐based foods that can now be applied to the dietetic management of vegetarians/vegans requiring a low FODMAP diet. Food processing lowered the FODMAP content of foods, thereby increasing options for patients following a low FODMAP diet.